2017
DOI: 10.18433/j3sq0b
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pharmacist-led Anticoagulation Management on Clinical Outcomes: A Systematic Review and Meta-Analysis

Abstract: -OBJECTIVES:We performed this systematic review and meta-analysis to confirm whether patients benefit more from pharmacist-led anticoagulation management than other models. METHODS: We searched PubMed, Embase, Cochrane Library and reference lists of yielded results conducted up to April 25, 2017. RCTs and observational cohort studies and case-control studies which compared the percentage of time within the target therapeutic range (TTR), the percentage of time within the expanded therapeutic range (TER), haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The assessment methods [21] included the following items: (1) Experimental design, (2) Risk of bias, (3) Inconsistency, (4) Indirectness, (5) Imprecision, and (6) Publication bias. The quality was assessed by two independent reviewers (J.H, Y.Z).…”
Section: Literature Quality Assessmentmentioning
confidence: 99%
“…The assessment methods [21] included the following items: (1) Experimental design, (2) Risk of bias, (3) Inconsistency, (4) Indirectness, (5) Imprecision, and (6) Publication bias. The quality was assessed by two independent reviewers (J.H, Y.Z).…”
Section: Literature Quality Assessmentmentioning
confidence: 99%
“…Different models of anticoagulation management services have been developed to improve the clinical outcomes of warfarin therapy. Based on observational studies, pharmacist‐managed anticoagulation services enhance INR control and reduce the rates of total bleeding and thromboembolic events when compared with other models . However, a meta‐analysis of eight randomised controlled trials (RCT) fails to demonstrate superiority of pharmacist‐led services in improving these outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Based on observational studies, pharmacist‐managed anticoagulation services enhance INR control and reduce the rates of total bleeding and thromboembolic events when compared with other models . However, a meta‐analysis of eight randomised controlled trials (RCT) fails to demonstrate superiority of pharmacist‐led services in improving these outcomes . Most of the existing studies were conducted in Western countries, with only one RCT targeting Chinese patients in Hong Kong .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other models to assess the quality of anticoagulation. Hou et al 26 performed a systematic review of 8 clinical trials and 9 observational studies and observed that the risk of thromboembolic and bleeding events significantly decreased in patients where the anticoagulation management was based on pharmacist-led management compared to the anticoagulation clinics or treatment with GPs. Conversely, many studies have reported improvements in the quality of oral anticoagulation with self-testing and selfmanagement approaches, with possible improvements in clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%